CFD simulation of fluid dynamic and biokinetic processes within activated sludge reactors under intermittent aeration regime. (1st August 2018) - Sánchez, F.; Rey, H.; Viedma, A.; Nicolás-Pérez, F.; Kaiser, A.S.; Martínez, M.
Abstract: Due to the aeration system, biological reactors are the most energy-consuming facilities of convectional WWTPs. Many biological reactors work under intermittent aeration regime; the optimization of the aeration process (air diffuser layout, air flow rate per diffuser, aeration length …) is necessary to ensure an efficient performance; satisfying the effluent requirements with the minimum energy consumption. This work develops a CFD modelling of an activated sludge reactor (ASR) which works under intermittent aeration regime. The model considers the fluid dynamic and biological processes within the ASR. The biological simulation, which is transient, takes into account the intermittent aeration regime. The CFD modelling is employed for the selection of the aeration system of an ASR. Two different aeration configurations are simulated. The model evaluates the aeration power consumption necessary to satisfy the effluent requirements. An improvement of 2.8% in terms of energy consumption is achieved by modifying the air diffuser layout. An analysis of the influence of the air flow rate per diffuser on the ASR performance is carried out. The results show a reduction of 14.5% in the energy consumption of the aeration system when the air flow rate per diffuser is reduced. The model provides an insight into the aeration inefficiencies produced within ASRs. Graphical abstract: Highlights: A CFD model of an activated sludge reactor is developed. The model simulates fluid dynamic and biokinetic processes within the reactor. Simulations are carried out under intermittent (transient) aeration regime. An assessment of the power consumption under different aeration conditions is done.